Demand, Institutional Capacity, and Program Viability for a Doctor of Philosophy in English Language Education - Elreen Aguilar-Delavin (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This convergent mixed-methods study examined the feasibility of offering a Doctor of Philosophy in English Language Education at the Graduate School of Dr. Emilio B. Espinosa Sr. Memorial State College of Agriculture and Technology (DEBESMSCAT) in Masbate, Philippines. A total of 128 education stakeholders answered a questionnaire covering respondent characteristics, 19 five-point feasibility indicators, and open-ended questions. Frequencies, percentages, and weighted means were used for the quantitative data, while written responses were analyzed thematically. Respondents rated all five domains very highly: market demand, resources and infrastructure, curriculum and course structure, potential impacts and outcomes, and overall feasibility. The strongest results concerned the program’s relevance to current educational needs, its expected contribution to institutional reputation and professional leadership, and the recommendation to proceed. The qualitative data, however, placed clear conditions on implementation, particularly faculty sufficiency, research resources, affordability, flexible access for participants from distant municipalities, and careful program sequencing. Under the stated assumptions, the six-year projection produced positive annual balances and a cumulative net balance of PHP 914,700. The program appears viable, but its opening should follow regulatory approval, verified faculty and resource capacity, a defensible cost plan, and continuing quality assurance.